Customary Law, Women's Rights and Traditional Courts in Cameroon - Temngah, Joseph (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1996)
This article highlights the controversy over Women's Rights in Cameroon given that women are regarded as a man's property under customary law. The article points out the position of women's rights under statutory law. It compares both rules without settling for either of them. Both rules are sources of Cameroonian law and are administered concurrently by the courts. Again, this article shows the awareness women have demonstrated by challenging the customary law position which considers a woman as an object. Finally, the article settles for the codification of laws notwithstanding the difficulties involved in this exercise, especially in a bi-jural state like Cameroon.